Long term analysis of N2O emission from partial nitritation anammox process under oxygen limitation. (December 2022) - Lang, Longqi; Sebilo, Mathieu; Bounouba, Mansour; Dubos, Simon; Sperandio, Mathieu
Abstract: Partial nitritation with anammox (PNA) process was achieved during 300 days to investigate the fate of N2 O and NO. N2 O emission factor increased from 0.4 ± 0.1 % up to 6.1 ± 0.3 % during intensification phase of 5 months and progressively stabilized at 2.0 ± 0.1 % after 10 months without any significant emission of NO. The emission of N2 O correlated with the ammonium consumption rate and the oxygen transfer rate. Experiment carried out in anoxic condition suggested that heterotrophic denitrification poorly contributed. Measurements of δ 15 N, δ 18 O and SP of N2 O demonstrated that its production resulted from the reduction of nitrite. The stimulating effect of nitrite on N2 O production was demonstrated with specific tests and observed during transient nitrite accumulation periods. This study highlighted the importance of nitrite and oxygen transfer rate control for future control strategies aiming to mitigate N2 O emission in PNA system. Graphical abstract: Unlabelled Image Highlights: N2 O EF slowly increased from 0.4 ± 0.1 % up to 6.1 ± 0.3 % within 5 months. EF is correlated to NH4 + uptake rate, O2 transfer rate and NO2 – concentration. Nitrite reduction was the main pathway for high N2 O emission. EF stabilized at 2.0 ± 0.1 % on a long term after increase of air flow rate. Long term experiments are necessary to assess N2 O emission from PNA system.